Improvement of beef cattle through breeding methods. - Smith, W.; Smith, E.; Ibsen, H.L.; Holland, L. (Kansas Agricultural Experiment Station, 2012)
The purebred Shorthorn herd maintained at Manhattan is being used as a primary basis for the purebred cattle breeding investigations which started at the Kansas station three years ago. The project is still in its preliminary stages, and the systems of breeding which have been adopted were regulated primarily by the pedigrees of the foundation females in the original college herd. The project has been designed to facilitate the collection of product. ion data which will be used to devise testing and breeding procedures useful to cattlemen for the improvement of beef cattle, through breeding methods.
Keywords: Beef; Breeding; Inbreeding; Performance